Government Policy In The Development And Development Of Tourism In Medan City - Arfiany Sepyanty Putri Nasution; Sri Mutia Fazira; Fadhila Putri Kaban; Hamdani, Hamdani; Sari Wulandari (Jurnal Multidisiplin Sahombu, 2024)
Medan’s tourism industry faces a number of challenges, including poor destination management, lack of funding, lack of advertising, poor infrastructure, lack of public awareness, and weak government oversight. Although places like Medan Zoo, Al-Mashun Grand Mosque, and Tjong A Fie Mansion have excellent tourism potential, overcoming these challenges requires collaboration between the public sector, corporations, and the government. The secret to maximizing Medan’s tourism development is teamwork that emphasizes promotion, strengthening human resources, improving infrastructure, and sustainable management.